MODELING AND NUMERICAL SIMULATION OF WOOD TORREFACTION - Pétrissans, Anélie; Hamada, Joël; Chaouch, Mounir; Gérardin, Philippe; Pétrissans, Mathieu (Innovation in Woodworking Industry and Engineering design, 2014)
Torrefaction is a thermal treatment step in a relatively low temperature range of 210–240˚C, which aims to improve the dimensional stability and durability of wood. The weight loss kinetics for torrefaction of wood samples was studied using equipment specially conceived to measure mass losses during thermal treatment. Laboratory experiments were performed un-der nitrogen. A mathematical model for the kinetics of the thermodegradation process was used and validated. Measurements of temperature distribution and weight loss were performed sam-ple of poplar wood during pyrolysis in an inert atmosphere at 230°C. The mathematical formu-lation describing the simultaneous heat and mass transfers requires coupled nonlinear partial differential equations. These unsteady-state mathematical model equations were solved numer-ically by the commercial package FEMLAB. A detailed discussion of the computational model and the solution algorithm is given. Once the validity of different assumptions of the model had been analyzed, the experimental results were compared with those calculated by the model. Acceptable agreement was achieved.